Effects of heat transfer surface temperature on liquid egg yolk fouling - Eakasit Sritham; Navaphattra Nunak; Worapanya Suthanupaphwut; Badin SOMLITSOPAK; Jedsada Chaishome; T. Suesut (Engineering in Agriculture Environment and Food, 2024)
This study was aimed at investigating the effects of different surface temperatures (60-80 C) on the formation of egg yolk deposits on heat transfer surface.Experimental data from the fouling period were fitted with zero-and first-order reaction models and the reaction kinetics of fouling was obtained using the Arrhenius equation.Egg yolk fouling curves exhibited an asymptotic pattern showing only fouling and post-fouling periods.The fouling resistance at transition point increased with the increasing surface temperature.The zero-order reaction model was well describing the reaction rate of egg yolk fouling.The obtained activation energy of 85.47 kJ/mol was less than that for thermal denaturation of egg yolk proteins.The fouling process of egg yolk was mainly controlled by the deposition reaction.
Keywords: Reproductive biology and impacts on aquatic species; Magnetic and Electromagnetic Effects